International Law Regulation of Environmental Security in Disarmament Treaties - A. V. Kukushkina (Московский журнал международного права, 2024)
INTRODUCTION. Currently, one of the urgent issues on the agenda is environmental protection. In the 80s 20th Century, due to the sharp degradation of the environment, the world community raised the issue of developing a concept of environmental safety. It has been integrated into the comprehensive system of international security as one of the constituent elements that is becoming increasingly important.The absence of lasting peace, the spread of armed conﬂicts, and the accumulation of weapons, including nuclear weapons, are of concern to the international community. Therefore, an important task in improving the system of international legal regulation of environmental protection is to improve its contractual basis.MATERIALS AND METHODS. This study uses the works of both domestic and foreign experts in international law and analyzes international legal documents on disarmament. In the course of the study, general scientiﬁc methods of cognition were used, which made it possible to systematically and logically study the subject of research in interrelation, interdependence and interdependence (comparative legal, formal legal methods, analysis, synthesis, induction, deduction).THE RESULTS OF THE STUDY. Within the framework of this article, the author analyzed the problem of international legal environmental protection in relation to disarmament and made proposals for their solution and further development of international legal regulation.JUDGMENTS AND CONCLUSIONS. According to the results of the study, it was found that treaties adopted in international law to ensure international security contribute not only to the maintenance of peace, but also to environmental safety, which over the past 30 years has become included in most international legal documents.